Efektifitas senam kaki diabetik dengan bola plastik terhadap tingkat sensitivitas kaki pada Pasien diabetes melitus tipe 2 - Oktaviah, Dewi -; Hasneli, Yesi -; -, Agrina - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of the research is  to analize the effect of diabetic foot exercises with plastic ball on the level of foot sensitivity in diabetic patients. The research used quasy experiment design with non-equivalent control group which divided into experimental group and control group. Sample of this research is 30 people divided into 15 people as the experimental group and 15 people as a control group. Sample in this research was taken by purposive sampling of techniques sampling which selected based on inclusion criteria. Instruments of this research was using monofilament in both groups to measuring respondent foot sensitivity. The experimental group were given interventions with diabetic foot exercises with plastic ball three times in 1 week. Data then analyzed into univariate and bivariate using dependent sample t test and independent sample t test. The result of the reearch showed that mean level of foot sensitivity before diabetic foot exercises with plastic ball was 8.467 points and mean level of foot sensitivity after diabetic foot exercises with plastic ball was 9.007 point mean an increase in the foot sensitivity after given intervention with p value  0,002 (<0,05). In conclusion diabetic foot exercises with plastic ball are effective against increasing the foot sensitivity in patients with diabetes mellitus type 2. The result is expected to be one of the nursing intervention to improve the foot sensitivity for patients with diabetes mellitus type 2. Keywords: diabetes mellitus, diabetic foot exercises, foot sensitivity